Desempenho e otimização de sistema de lodos ativados para tratamento de efluente industrial - Firmino, Cristiano Benevides (Universidade Federal Rural do Semi-Árido, 2019)
The treatment of the effluents generated in the production processes to suit the legal standards of launching has become a great concern of the companies. In addition to strict compliance with environmental legislation, another equally important aspect is the image of the company with public opinion, customers and society in general, more and more attentive and demanding, mainly due to the easy access to the information disclosed by the media. The need for the study arose from the urgency to reduce the time needed to remove the organic load that the current configuration of the treatment plant provided. In this context, the present study aims to evaluate the efficiency of the treatment system of industrial tributaries with the application of activated sludge to comply with current environmental legislation, as well as to promote reuse conditions for the treated effluent. During the monitoring of the system were used 4 treatments: treatment with Moringa oleifera; PAC treatment with addition of anionic polymer; and LA treatment in two stages, the phase of acclimatization of biomass and full operation. With the results, it was possible to observe that even the LA system requiring a higher TDH than the others, the treatment becomes feasible, since it promoted greater efficiency in the removal of the studied parameters, COD, SST and Ammoniac Nitrogen. As a measure of reuse of treated effluent, it was proposed the use of hydroponic and semi hydroponic systems, potentializing the use of the effluent even without compliance with legislation. It is worth noting that this measure could generate profits for the company, since the production of these systems can be used for food. Thus, the results were satisfactory and can serve as a basis for future studies, and may subsidize the choice of a treatment that may be chosen by other enterprises.
Keywords: Tratamento biológico, Demanda Química de Oxigênio, Moringa oleífera, Policloreto de Alumínio, Reuso.; Biological treatment, Chemical Oxygen Demand, Moringa oleifera, Aluminum Polychloride, Reuse.; ENGENHARIAS::ENGENHARIA SANITARIA